Laudatio: Miguel Julve and Francisco Lloret, a Friendly Pair of Two Exceptional Coordination Chemists in Molecular Magnetism - Michel Verdaguer (Magnetochemistry)
This laudatio is dedicated to Professors Miguel Julve Olcina and Francisco Lloret Pastor on the occasion of their retirement in 2024. The first part deals with the scientific trajectory of the Coordination Chemistry team at the University of Valencia, within the Department of Inorganic Chemistry on the Burjassot campus and then in the Paterna Institute of Molecular Science. The second part relates some of the more salient results of the heritage left by our two colleagues in molecular magnetism, where they developed, in their own way, a rational approach to designing, creating and understanding a wealth of brand new systems from the simplest to Multifunctional Molecule-based Magnetic Materials. The robust and friendly links between our two colleagues are emphasized in the third part.